Pengembangan Cerita Rakyat Melayu dalam Bentuk E-Book sebagai Upaya Meningkatkan Literasi Digital - Uli, Indriyana; Kusnita, Sri; Yuniarti, Netti (JP-BSI (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
This research aims to develop reading materials in the form of e-books that can help in improving the digital literacy movement in universities. The e-book used for this research is a collection of Malay folklore in Mempawah Regency. This research is a type of development research known as Research and Development or R and D. This research uses a development model in the form of the Alensi and Trollip models. The population in this study was students of the Indonesian Language and Literature Education study program IKIP PGRI Pontianak. The sample in this study was 2nd semester students of the IKIP PGRI Pontianak Indonesian Education study program. Data analysis techniques in this study are in the form of validity and student response in an effort to increase digital literacy. This research produced Malay folklore in Mempawah regency in the form of an e-book as an effort to improve digital literacy in students of the Indonesian language and literature education study program. The development of Malay folklore in Mempawah Regency in the form of e-books as an effort to improve digital literacy in students of the Indonesian Language and Literature Education Study Program IKIP PGRI Pontianak achieved very valid and very effective criteria as an effort to increase student digital literacy.